KOMUNIKASI POLITIK SENIMAN BONDRES PADA PEMILU LEGISLATIF 2014 (STUDI KASUS : I KADEK ARIMBAWA) - Hermanus, Rainhard Rolando; Ali Azhar, Muhammad; Bandiyah, Bandiyah (Jurnal Nawala Politika; 2019, 2019)
ABSTRACT Bond res artist I Kadek Arimbawa took the opportunity to become a member of the 2014 DPD RI through the media of Bondres, which is a mask performing art featuring funny characters who gave message, ethics, morals and information. This study discusses Bondres artists who have the popularity of art until their choice to become members of the 2014 DPD RI. The theory in this study is the theory of political communication and discourse analysis theory in which I Kadek Arimbawa's message to the public when ngayah activities with the Bali Art Foundation with performing arts media Bondres and its effect are the electability as a member of the 2014 DPD RI. Then in the discourse analysis the language used is a language that is able to influence the public in communication and I Kadek Arimbawa as a communicator can control the community through the discourse in ngayah I Kadek Arimbawa. The research method used is a descriptive qualitative design method and provides an overview of political communication with Bondres performing arts media and analyzed by collecting data, reducing, presented and drawing conclusions. The results of this study indicate: First, political communication I Kadek Arimbawa uses Bondres media with its social activities namely ngayah in pakraman village in Bali and successfully selected to be a member of the DPD RI. Second, the political communication of I Kadek Arimbawa as an Bondres artist, which takes place during penyanggra or before the Bondres performance and evaluation of the buffer during the performance. Through political communication and direct social interaction with the community, people sympathize to elect I Kadek Arimbawa in the 2014 Legislative Election. Keywords: Bondres, I Kadek Arimbawa, Political Communication, DPD RI